e-Movement Book Application - Vedvanita Khamageet; Dr S R Raja (International Journal of Scientific Research in Science, Engineering and Technology, 2025)
The e-Movement Book is an innovative application to keep track of officers leaving office during office hours to attend official meetings, conferences and workshops, or external engagements. It serves as a comprehensive record of their movements and activities to accountability and transparency and efficient operations. Main purpose of the system is to monitor and restrict unauthorised movements of officers. The e-Movement application documents names of the officer, the specific dates and times of departures and arrivals, including the location of meeting venues, somewhat details